A simple preparation of porous graphene nanosheets containing onion-like nano-holes with favorable high-rate Li-storage performance. Issue 68 (4th July 2016) - Song, Ranran; Cao, Bin; Zhang, Di; Song, Huaihe
Abstract : Porous graphene nanosheets containing hollow onion-like nano-holes were fabricated through simple graphitization from phenolic resin, and exhibit endurable capability and outstanding rate performance as anode materials for lithium ion batteries. Abstract : Porous graphene nanosheets (PGNs) containing onion-like nano-holes were simply prepared using copper nitrite as template and phenolic resin as carbon source by graphitization at 2800 °C. Based on the investigations of morphology and structure, PGNs were used as anode materials for lithium-ion batteries, and it was found that this PGN electrode exhibits a stable voltage plateau, endurable Li-storage capability and outstanding rate performance of 258 mA h g −1 at 1 A g −1 and 105 mA h g −1 at 10 A g −1 after 700 cycles, superior to those of other carbon anodes with a low voltage plateau. The reasons are discussed and explained in detail.